Coherent anti-Stokes Raman spectroscopy of diamond - Viranna, Narendra Balaguru (Department of Physics, 2017)
Experiments were performed to investigate Coherent Anti-Stokes Raman Scattering (CARS) in diamond. Aspects of this type of non-linear scattering are presented theoretically, and various experimental configurations were attempted in order to study them. These included the dependence of the CARS signal intensity on the intensities of the two exciting frequency-doubled Nd:YAG (pump) and dye (Stokes) lasers, the variation of the CARS signal polarization as a function of the lasers' polarization, and the dependence of the CARS signal intensity on the phase mismatch of the laser beams. The phase mismatch measurement confirmed the predicted sinc² nature of the CARS signal intensity, while· the polarization measurements provided new information on the ratio of the non-vanishing components of the cubic susceptibility x³ of diamond. The CARS signal intensity was found to change linearly with the dye laser intensity and quadratically with the Nd: Y AG laser intensity. The CARS signal was found at the predicted 1332 cm⁻¹ shift from the doubled Nd:YAG emission, and its linewidth of 1.2 cm⁻¹ is in agreement with the spontaneous Raman linewidth.The spectral data were fitted to a modified Voigt profile containing the non-resonant cubic susceptibility contribution, and this allowed us to establish the ratio of the resonant and non-resonant parts of x³. An attempt to generate Stimulated Raman Scattering in diamond was unsuccessful.